Analysis of Factors Inhibiting MSME Exports in the Culinary Sector to Enter the Global Market - Deswitasari, Anisa; Usman*, Usman; Hariyadi, Guruh Taufan (Universitas Syiah Kuala, 2024)
MSMEs are currently the most developed commercial sector in the local market. The sector that is most in demand and survives in the local market is the culinary sector. However, culinary MSMEs have the lowest share in the global market. Lack of potential exporter capacity and products that do not meet export standards as well as a lack of export financing are currently the main obstacles for SMEs. This research aims to help prospective exporters with an overview of exporting their products on the global market as well as the export standards and procedures that must be followed, as well as providing solutions for export organizations to provide a more efficient export platform. This research uses data collection techniques through qualitative methods with primary data and secondary data. The research results show that exported products do not meet HACCP standards and food safety licenses in several countries. strict export procedures that must be followed by culinary MSMEs with relatively low human resources. Export stakeholders do not yet have sufficient skills to compete in the export market, and MSME stakeholders also do not have sufficient knowledge regarding Export Pro.